Shaping Blended Learning in Russia Undergraduate Technical Education; SGEM. 2nd International Multidisciplinary Scientific Conference on Social Sciences and Arts; Bk. 1, Vol. 2 - Krasnova T. I. Tatiana Ivanovna (Education and Educational research, 2015)
Title screen